2005
DOI: 10.1002/jmr.690
|View full text |Cite
|
Sign up to set email alerts
|

Peptide self-aggregation and peptide complementarity as bases for the evolution of peptide receptors: a review

Abstract: This paper reviews the three major theories of peptide receptor evolution: (1) Dwyer's theory that peptide receptors evolved from self-aggregating peptides; (2) Root-Bernstein's theory that peptide receptors evolved from functionally and structurally complementary peptides; and (3) Blalock's theory that receptors evolved from hydropathically complementary sequences encoded in the antisense strand of the DNA encoding each peptide. The evidence to date suggests that the co-yevolution of peptides and their recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
67
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(75 citation statements)
references
References 100 publications
2
67
1
Order By: Relevance
“…Novelty will be built in general from mixing and matching previously adaptive modules into evermore elaborate hierarchies of complexity. (87)(88)(89)(90) Experimental tests of composomal ecology Many possible tests, some retrodictive (that is regarding patterns that should exist within data already available) and some predictive, exist to differentiate our theory from other theories of the origins of life. We propose only a handful here.…”
Section: Modularity and Emergent Propertiesmentioning
confidence: 99%
“…Novelty will be built in general from mixing and matching previously adaptive modules into evermore elaborate hierarchies of complexity. (87)(88)(89)(90) Experimental tests of composomal ecology Many possible tests, some retrodictive (that is regarding patterns that should exist within data already available) and some predictive, exist to differentiate our theory from other theories of the origins of life. We propose only a handful here.…”
Section: Modularity and Emergent Propertiesmentioning
confidence: 99%
“…VWF and pgp1b do not appear to bind to each other according to hydropathic complementarity (data not shown). We have previously demonstrated that hydropathic complementarity cannot explain insulin -glucagon complementarity, nor the ability of these proteins to self-aggregate (Root-Bernstein 2005b). And there is clearly no application of the antisense concept to the interaction of myelin basic protein with MDP or other bacterial cell-wall derived adjuvants, which are primarily polysaccharide based.…”
Section: Discussionmentioning
confidence: 99%
“…They independently isolated, from cDNA libraries, identical DNA clones encoding single polypeptide receptors with dual peptide binding sites. 9,11 The MRT theory is controversial 29,30 and was not confirmed in the case of Ang II, vasopressin and other receptors. 30,31 Most evidence for the MRT is based on immunological techniques 30 and these methods are subject to question as mentioned above.…”
mentioning
confidence: 99%
“…Moreover, many putative receptors isolated according to MRT theory have not turned out to be receptors. 30 This questions the universal applicability of MRT.…”
mentioning
confidence: 99%